2014
DOI: 10.1002/ana.24246
|View full text |Cite
|
Sign up to set email alerts
|

Early treatment is associated with improved cognition in Hurler syndrome

Abstract: Early age at transplantation is a strong predictor of cognitive, language, and adaptive behavior outcomes. Children younger than 9 months at the time of transplant showed normal cognitive development. Our results demonstrate that early diagnosis is necessary for optimal outcomes and support the need for newborn screening, because most patients are not identified at this young age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
94
0
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(108 citation statements)
references
References 37 publications
2
94
0
12
Order By: Relevance
“…Several factors were associated with a better prognosis after HSCT: gross motor function preserved, IQ of at least 85, and age at onset older than four years. Mean (range) *Disease duration = the difference between age at onset of cerebral signs and age at HSCT (see Table 2 Early transplantation has been related to optimal long-term cognitive and language outcomes in MPS-IH 9,14 . Although our MPS-IH survivor (patient MPS-IH-10) was a late transplanted patient, her follow-up four years later was very encouraging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several factors were associated with a better prognosis after HSCT: gross motor function preserved, IQ of at least 85, and age at onset older than four years. Mean (range) *Disease duration = the difference between age at onset of cerebral signs and age at HSCT (see Table 2 Early transplantation has been related to optimal long-term cognitive and language outcomes in MPS-IH 9,14 . Although our MPS-IH survivor (patient MPS-IH-10) was a late transplanted patient, her follow-up four years later was very encouraging.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in fibroblasts from MPS-I patients with different phenotypes and different genetic backgrounds confirmed that tiny differences in residual enzyme activity are related to important clinical differences 33 . Several studies on HSCT in MPS-IH reported improvements in cardiopulmonary function, hearing and vision, and preservation of neurocognitive function 9,14,34 . Some of them documented that subsequent cognitive deterioration might occur after HSCT, mostly if it is performed late 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also demonstrated benefits for Hurler syndrome, with transplantation before 9 months of age associated with improvements in cognitive function, receptive and expressive language, and adaptive behavior (Poe et al 2014). Early treatment may have similar effects for some of the somatic manifestations of Hurler syndrome, but whether orthopedic complications can be prevented remains to be elucidated.…”
Section: Discussionmentioning
confidence: 81%
“…In general, multi‐systemic and progressive signs and symptoms should raise suspicion of a genetic disorder, including a lysosomal storage disorder such as MPS I 8. The benefits of early treatment with haematopoietic stem cell transplantation (HSCT) in patients with severe MPS I include substantial changes in the disease course along with improved cognition 9, 10, 11. Early treatment of patients with MPS I can also slow disease progression and improve patient outcomes, including quality of life 12.…”
Section: Introductionmentioning
confidence: 99%